Mortality and Discharge Outcome in Acute Myocardial Infarction Patients: A Study Based on Korean National Hospital Discharge In-Depth Injury Survey Data - Hwang J; Lee K (Dove Medical Press, 2024)
Jieun Hwang,1,2 Kyunghee Lee3 1Department of Health Administration, College of Health Science, Dankook University, Cheonan City, Chungcheongnam-do, South Korea; 2Institute of Convergence Healthcare, Dankook University, Cheonan City, Chungcheongnam-do, South Korea; 3Department of Healthcare Management, Eulji University of Korea, Seongnam City, Kyeonggi-do, South KoreaCorrespondence: Kyunghee Lee, Department of Healthcare Management, Eulji University of Korea, 553 Sanseongdaero, Sujeong-Gu, Seongnam City, Kyeonggi-do, 13135, South Korea, Tel +821072428346, Email rose1294@hanmail.netPurpose: The aim of this study was to analyze hospital-discharged acute myocardial infarction (AMI) patients in Korea (2006- 2020) to understand how pre-existing conditions affect mortality rates.Participants and Methods: This study utilized the 2006- 2020 Korean National Hospital Discharge In-depth Injury Survey data. A weighted frequency analysis estimated discharged AMI patients and calculated age-standardized discharge and mortality rates, Charlson Comorbidity Index (CCI) score distribution, and general patient characteristics. Weighted logistic regression analysis examined influencing mortality factors.Results: There were 486,464 AMI patients (143,751 female), with AMI-related mortality rates at 7.5% (36,312): 5.7% for males (19,190) and 11.8% for females (17,122). The highest mortality rate was among individuals aged 70- 79 years (25%). Factors influencing mortality included sex, insurance type, admission route, hospital bed count, region, operation status, and CCI score. Mortality risk at discharge was 1.151 times higher in females than males (95% CI: 1.002- 1.322), 0.787 times lower among those with national health insurance than Medicaid recipients (95% CI 0.64- 0.967), 2.182 times higher among those admitted via the emergency department than the outpatient department (95% CI 1.747- 2.725), and 3.402 times higher in patients with a CCI score of 3 points than those with 0 points (95% CI 1.263- 9.162).Conclusion: The number of discharged AMI patients and related mortality rates increased, underscoring the need for proactive management of chronic diseases, particularly for those with higher CCI scores.Keywords: acute myocardial infarction, mortality, Charlson Comorbidity Index (CCI), chronic diseases, Korean National Hospital Discharge In-depth Injury Survey data